2000
DOI: 10.1177/016173460002200303
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Ultrasound Elasticity Imaging for Renal Transplant Diagnosis: Kidney Ex Vivo Results

Abstract: It may be possible to diagnose and monitor scarring, inflammation and edema in transplant kidney using reconstructive ultrasound elasticity imaging. Kidney elasticity is expected to change dramatically with scar, and to a lesser degree, with acute inflammation and edema. The hypothesis that changes in kidney elasticity can be imaged using a clinical ultrasound scanner was experimentally tested with an ex vivo canine kidney model, and results on a single pair of kidneys are reported in this paper. A cross-linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
1
25
2
Order By: Relevance
“…12,24,25 However, a human study using transient elastography and an ex vivo study of canine kidneys showed similar mean stiffness values as our study. 21,28 In fact, the Young modulus used in this study could be measured differently according to the radio frequency of shear waves even in the same tissue or organ. 29 Magnetic resonance elastography uses mechanical vibration to create shear waves in the organs and quantifies the shear modulus.…”
Section: Discussionmentioning
confidence: 99%
“…12,24,25 However, a human study using transient elastography and an ex vivo study of canine kidneys showed similar mean stiffness values as our study. 21,28 In fact, the Young modulus used in this study could be measured differently according to the radio frequency of shear waves even in the same tissue or organ. 29 Magnetic resonance elastography uses mechanical vibration to create shear waves in the organs and quantifies the shear modulus.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical situation is exacerbated by the fact that substantial renal parenchymal loss may occur before there is any change in functional measurements of renal function [24] . Previous ex vivo studies have suggested that ultrasound elasticity imaging may be able to detect localized elastic changes within the kidney [25,26] . Since the fi brosis associated with CAN may be accompanied by an increase in measurable elastic tissue properties, such as shear or Young's modulus, elasticity imaging may provide a means of measuring renal fi brosis and diagnosing or monitoring CAN [25,26] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous ex vivo studies have suggested that ultrasound elasticity imaging may be able to detect localized elastic changes within the kidney [25,26] . Since the fi brosis associated with CAN may be accompanied by an increase in measurable elastic tissue properties, such as shear or Young's modulus, elasticity imaging may provide a means of measuring renal fi brosis and diagnosing or monitoring CAN [25,26] . Therefore, we applied ultrasound elasticity imaging to several renal transplant recipients to see if this method could practically detect differences in the elastic properties of renal parenchymal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, speckle tracking was optimized by largely constraining tissue motion to the area along the beam because along-beam (axial) resolution was finer than across-beam (lateral) resolution for the images used in this study. The finer axial resolution provides better tracking accuracy and noise robustness along the beam compared with tracking across the beam (Emelianov et al 2000). To improve speckle tracking, we used a high frame rate (.30 frames/s), emphasized temporal resolution (space-time setting as T2 on Sequoia ultrasound scanner) and used low grayscale frequency (2-3.5 MHz) as standard parameters in the study.…”
Section: Doppler Parameters and Real-time Ultrasound Data Acquisitionmentioning
confidence: 99%